The Coptic Monastery at the First Pylon of Karnak Temple - Ghaly, Emad.
In the second half of the first century early Christianity was on the rise in Egypt. From this time on early Christians of Egypt adapted their life, art, habits, names, daily life language, and worship. Christianization of ancient pagan sites became a phenomenon within the Roman Empire. Early Christians reused ancient temples and tombs as parts of monasteries and cities. Egypt is a special case when talking about temple conversion in late antiquity. This study focuses on the early Christian reuse at the first pylon of Karnak temple on the city of Luxor in Upper Egypt.  doi: http://dx.doi.org/10.5913/jarce.53.2017.a005